Scalar Diversity, Negative Strengthening, and Adjectival Semantics - Gotzner, Nicole; Solt, Stephanie; Benz, Anton (Frontiers in Psychology, 2018)
Previous research has demonstrated great variability in the rates of scalar inferences across different triggers [Doran et al., 2009, van Tiel et al., 2016]. In the current study, we show that variation is more systematic than previously thought. In particular, we present experimental evidence suggesting that endorsements of scalar implicatures (i) are anti-correlated with the degree of negative strengthening of the stronger scale-mate (e.g., whether John is not stunning is interpreted as conveying that John is rather ugly) and (ii) are affected by the scale structure and the underlying scalar semantics of gradable adjectives (in particular boundedness, polarity and adjectival extremeness). Overall, our research suggests that scale structure should be taken into account in theories of implicature.